Gambaran Penyakit Infeksi Bakteri dan Penggunaan Antibiotik pada Anak di Rumah Sakit Umum Cut Meutia Aceh Utara Tahun 2022 - Nabila Az-zahra; Mauliza Mauliza; Mardiati Mardiati (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2026)
Bacterial infections are diseases that can be transmitted by bacteria from sufferers to others, either directly or indirectly. Cases of bacterial infections are more common among children. The use of antibiotics is needed to treat life-threatening conditions caused by bacteria by killing bacteria or making it difficult for bacteria to grow and reproduce. Antibiotics are a type of drug given to prevent bacterial infections, or are drugs given to high-risk patients. This research method is a descriptive study by collecting medical record data to find out the description of bacterial infections and the use of antibiotics in pediatric inpatients at RSU Cut Meutia Aceh Utara in 2022. This research technique used purposive sampling with a sample size of 183 samples. The results of this study showed that 183 children suffered from bacterial infections and received injection antibiotic therapy, the majority were boys, namely 106 children (57%), the age group with the most number of sufferers, namely aged 0‒5 years, totaling 76 children (41%), the percentage of bacterial infections most commonly found in pediatric inpatient wards at RSU Cut Meutia Aceh Utara in 2022, namely typhoid fever as much as 33%, the class of antibiotics most commonly used at RSU Cut Meutia is cephalosporins (93%).